STRATEGI GURU DALAM MENGEMBANGKAN KETERAMPILAN MEMBACA PERMULAAN - Feni Juniarti; Hazarah Nabilah; M. Iqbal Arrosyad (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Using a qualitative approach involving semi-structured interviews with two first-grade elementary school teachers, coupled with participant observation and document analysis, this study demonstrates that strategies such as interactive media and differentiated approaches can improve reading skills by up to 75%, prompting the development of a teacher training module for national implementation. The purpose of this study was to identify and analyze the various strategies employed by teachers in developing early reading skills in first-grade elementary school students and to assess their effectiveness in improving students' learning motivation, phonics skills, and vocabulary comprehension. This study also aimed to uncover supporting factors and barriers to the implementation of reading learning strategies and develop recommendations for designing curricula and teacher training that are more inclusive and adaptive to basic literacy needs in various educational contexts. This study focused on identifying, analyzing, and evaluating teacher strategies in developing these skills, with an emphasis on their effectiveness in improving student motivation and abilities, and providing recommendations for an inclusive curriculum.